2013
DOI: 10.1167/iovs.12-11491
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nitric Oxide on Anterior Segment Physiology in Monkeys

Abstract: Citation: Heyne GW, Kiland JA, Kaufman PL, Gabelt BT. Effect of nitric oxide on anterior segment physiology in monkeys. Invest Ophthalmol Vis Sci. 2013;54:5103-5110. DOI: 10.1167/iovs.12-11491 PURPOSE. To determine the effect of the nitric oxide donor, sodium nitroprusside (SNP), and the nitric oxide synthase (NOS) inhibitor, L-nitro-arginine-methylester (L-NAME), on IOP, mean arterial pressure (MAP), pupil diameter (PD), refraction (Rfx), aqueous humor formation (AHF), and outflow facility (OF) in monkeys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
63
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 35 publications
2
63
0
Order By: Relevance
“…In human eyes, NOS reactivity was enriched in major sites of outflow resistance, including the TM and SC, as well as in collecting channels. 16 The NO-donating compounds effectively decrease conventional outflow resistance, leading to a decrease in IOP and outflow rate in different animal models, including rabbits, 21-24 pigs, 25 dogs, 22 and monkeys, 22,26 and in perfused postmortem human eyes. 27,28 Our previous study 29 further showed that eNOS/NO is a key regulator of outflow facility and…”
mentioning
confidence: 99%
“…In human eyes, NOS reactivity was enriched in major sites of outflow resistance, including the TM and SC, as well as in collecting channels. 16 The NO-donating compounds effectively decrease conventional outflow resistance, leading to a decrease in IOP and outflow rate in different animal models, including rabbits, 21-24 pigs, 25 dogs, 22 and monkeys, 22,26 and in perfused postmortem human eyes. 27,28 Our previous study 29 further showed that eNOS/NO is a key regulator of outflow facility and…”
mentioning
confidence: 99%
“…Independent lines of investigation consistently reported on the ability of NO to relax TM and Schlemm's canal (SC) that ultimately results in enhanced trabecular outflow facility. 7,9,15 Furthermore, NO seems to also affect AH formation at the ciliary epithelium. 6 Both these effects are mediated via soluble guanylyl cyclase activation and cGMP formation.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, several studies have reported that blockage of pre-junctional M2/M4 muscarinic receptors on cholinergic-nitrergic nerve terminals by atropine causes release of neural nitric oxide from the nerve terminals, followed by a vasodilation response in ocular blood vessels (Ayajiki et al, 2000;Toda and Nakanishi -Toda, 2007), as well as decreased contraction of trabecular meshwork cells forming conventional outflow cells (Ellis et al, 2010;Heyne et al, 2013). Further, Schlemm's canal endothelial cells are enriched with the NO-producing enzyme eNOS (Nathanson and McKee, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, immunohistochemical studies have shown an increased NOS activity in the longitudinal compared with the circular regions of the ciliary muscle in healthy human eyes (Nathanson andMcKee, 1995, Chen et al, 1998) and a dramatic decrease in NOS activity in human glaucoma eyes compared with control eyes (Nathanson and McKee, 1995, Chen et al, 1998, Heyne et al, 2013. Thus, it is possible that the lack of subsequent elevation of IOP after homatropine instillation in our study is related to a relaxation of longitudinal portion of the ciliary muscle that causes a decrease in tension transmitted directly to the trabecular meshwork and Schlemm's canal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation